Flare-up Rate of Necrotic Mandibular Molars in One and Two-Visit Endodontic Treatment Using Apex locater and NI-TI Files - Abdullah Al-Sharif (Wolters Kluwer Medknow Publications, 2011)
This study compared the flare-up rate of endodontically treated molar teeth with necrotic pulp, using a Root ZX apex locater and NI-TI files in one-visit versus two-visits. Root canal treatment was done in 251 patients (129 in one visit group and 122 in two visits) using the same technique and filling materials. Patients were asked to circle the type of pain in a written form after 24 and 48 hours and after one week of finishing the root canal treatment. Pain was reported by very few patients of both groups during the first 24 and 48 hours, which disappeared during one week. A statistically significant difference (P= 0.029) in the reported pain was found between the two groups. It was found to be more in the two visit group. It was concluded that both techniques have to be viewed as part of a total endodontic treatment spectrum. The choice of preferring one over the other has to be determined by the circumstances surrounding each individual case.